PENGARUH KUALITAS PELAYANAN DAN PERSEPSI HARGA TERHADAP KEPUASAN DAN WOM PASIEN DI RSU PRIMA MEDIKA - Tjintiadewi, Ni Kadek; Rahyuda, I Ketut (E-Jurnal Manajemen; Vol 7 No 11 (2018)DO - 10.24843/EJMUNUD.2018.v07.i11.p14, 2018)
This study aims to determine the effect of service quality and price perceptions on customer satisfaction and word of mouth in outpatients at RSU Prima Medika. This research was conducted in Denpasar City by using sample size of 100 people with non-probability method in the form of purposive sampling. Data collection was obtained from questionnaires distributed at RSU Prima Medika Denpasar by using 19 indicators and the indicators were measured using Likert scale. The data analysis technique used in this research that is path analysis (path analyis) and accompanied by test of classical assumption. The results of the study found that service quality and price perception partially have a positive and significant effect on customer satisfaction. In addition, service quality, price perception and customer satisfaction simultaneously have a positive and significant influence on word of mouth. Keywords : Service Quality, Price Perception, Customer Satisfaction, Word Of Mouth